Barriers to Foreign Direct Investment in Nepalese Hydropower: A Policy and Stakeholder Perspective - Pandey, Janak Prasad (Journal of Multidisciplinary Research Advancements, 2026)
Nepal possesses one of the world’s largest hydropower potentials (83,000 MW), yet less than 3,000 MW has been developed. While the government has introduced liberal policies such as the Foreign Investment and Technology Transfer Act (FITTA, 2019) and Bilateral Investment Promotion and Protection Agreements (BIPPA), actual foreign direct investment (FDI) inflows remain far below potential. This study identifies and analyses the barriers to FDI in Nepal’s hydropower sector from a policy and stakeholder perspective. Primary data were collected from 30 stakeholders in the Kathmandu Valley, including FDI-based hydropower companies, government authorities, commercial banks, Nepal Rastra Bank, Nepal Electricity Authority (NEA), legal and financial consultants, and private-sector associations. Quantitative rankings (5-point Likert scale) and qualitative thematic analysis of open-ended responses were employed. Findings reveal that economic barriers are perceived as the most severe (mean = 3.91), particularly high inflation (4.10) and lack of investment security (4.03), followed by political barriers such as frequent strikes (3.95) and government changes (3.85). NEA’s monopoly as regulator and single buyer of power was identified as a unique structural barrier. The central theme from qualitative analysis is a critical policy-practice gap: formal policies are liberal, but inconsistent implementation, bureaucratic discretion, land acquisition complexities, and transmission constraints deter investment. Stakeholders recommend establishing an independent energy regulator, simplifying licensing, amending land laws, and accelerating the development of transmission infrastructure. The study concludes that addressing implementation failures, not just policy content, is essential to unlock Nepal’s hydropower potential.